Effects of Landscape Compositional Heterogeneity and Spatial Autocorrelation on Environmental Niche and Dispersal in Simulated Organisms - Joseph Tardanico; Thomas Hovestadt (Ecology and Evolution)
ABSTRACT Local adaptation, environmental tolerance, and dispersal mutually influence the evolution of one another and each are in turn influenced by landscape spatial structure. While each of the three have been investigated frequently in isolation in relation to spatial structure, the three have rarely been considered together. In this study, we explored how the magnitude of landscape environmental heterogeneity (compositional heterogeneity), and environmental spatial autocorrelation jointly affect the evolution of environmental niche optima, tolerance, dispersal frequency, and dispersal distance using a spatially explicit individual based model simulating organisms living, reproducing, and dispersing within grid‐based fractal landscapes. Compositional heterogeneity tended to have the strongest influence over patterns while spatial autocorrelation typically played a mediating role. We found that niche adaptation and dispersal patterns were driven by a balance between pressure to avoid risk imposed by spatial heterogeneity and pressure to hedge against risk imposed by temporal environmental fluctuations. Dispersal frequency and dispersal distance were affected differently by spatial structure, underscoring the importance of considering the two independently.